Egg production, egg quality, and lipid peroxidation status in laying hens maintained at a low ambient temperature (6°C) and fed a vitamin C and vitamin E-supplemented diet - Küçük, Ömer; Şahin, Nurhan; Şahin, Kazım; Gursu, MF; Gulcu, F; Ozcelik, M; Issi, M (Czech Academy Agricultural Sciences, 2003)
This experiment was conducted to evaluate the effects of vitamin C (L-ascorbic acid) and vitamin E (alpha-tocopherol acetate) on egg production, egg quality, lipid peroxidation status (measured as MDA), and some serum metabolites in laying hens (Hy-Line) maintained at a low ambient temperature (6degreesC). One hundred and twenty laying hens (18-wk-old) were divided into four groups, 30 hens per group. The laying hens were fed either a basal diet or the basal diet supplemented with either 250 mg of L-ascorbic acid/kg of diet, 250 mg of a-tocopherol acetate/kg of diet or 250 mg of L-ascorbic acid plus 250 mg of a-tocopherol acetate/kg of diet. Although feed consumption of the hens was similar (P > 0.05) among treatments, supplemental vitamin C and E significantly increased final body weight, egg production, and improved feed efficiency (P < 0.05). Egg weights were also greater (P < 0.05) in hens supplemented with the combination of vitamin C and E than that of hens supplemented either vitamin or no vitamin (control). Haugh unit did not change upon each vitamin supplementation, but the combination of the vitamin supplement yielded a higher Haugh unit (P < 0.05). Each dietary supplement of vitamin C and vitamin E improved the egg quality (P < 0.05) resulting in a greater specific gravity, thicker egg shell, and heavier egg shell weight. Separately or as a combination, supplemental vitamin C and E decreased MDA, glucose, cholesterol, and triglyceride concentrations (P < 0.05). Results of the present study showed that supplementing vitamin C and vitamin E, particularly as a combination, improved the performance of cold-stressed laying hens, offering a potential protective management practice in preventing cold stress-related losses in performance of laying hens. Results of the present study also indicated that the effects of vitamin C and vitamin E are additive.
Keywords: cold stress; vitamin C; vitamin E; laying hen; egg production; lipid peroxidation